Evaluate the expression for h = –10 and j = 0. Simplify your answer.

hj
h + j
=

1 answer

To evaluate the expression given \( h = -10 \) and \( j = 0 \), we can substitute these values into the expression:

\[ \frac{hj}{h + j} \]

First, we calculate \( hj \):

\[ hj = (-10)(0) = 0 \]

Next, we calculate \( h + j \):

\[ h + j = -10 + 0 = -10 \]

Now we can substitute these results back into the expression:

\[ \frac{hj}{h + j} = \frac{0}{-10} \]

Since any number divided by a non-zero number is 0, we have:

\[ \frac{0}{-10} = 0 \]

Thus, the simplified answer is:

\[ \boxed{0} \]

Similar Questions
  1. how does a rodeo star get around??well if you cant give me an answer can you help me. heres the instructions First Simplify the
    1. answers icon 5 answers
  2. ***show workevaluate the expression: 7^-6 (-6)^-9 simplify the expression. write your answer using only positive exponents.
    1. answers icon 2 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions